POTENSI BAKTERI PELARUT FOSFAT DAN DIAZOTROF DARI RHIZOSFER KELAPA SAWIT TANAH GAMBUT SAPRIK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT - Ida Nur Istina; Happy Widiastuti; Heri Widianto (Jurnal Agroteknologi, 2020)
Utilization of biological fertilizer has the potential to reduce inorganic fertilizer application in oil palm cultivation. The aims of this research to obtain the potential of phosphate (P) solubilizing and diazotrophic bacteria from oil palm rhizosphere towards palm oil seedling growth. This research has been done on Sapric peat soil at Pelalawan Regency, Riau Province from June to November 2014, using a factorial randomized block design (3x5 with 3 replications). The first factor were the potential bacteria isolates (Io = without isolates; I1 = Isolate T5.1 + T7. I2 = Isolate T9.1 + T5); the second factor were NPK fertilizer dosage (p1-100%; p2 = 85%; p3 = 70% fertilizer and p4 = 55% recommended fertilizer). The results showed that sapric peat soil was a potential source of P solubilizing bacteria with the ability to solubilized of P up to 329.94 ppm, and diazotrophic bacteria with the ability of N-fixation up to 0.0293 mmol/L/ hr.  Application of 70% N and P fertilizers and i2 isolate provides the best vegetative growth performance of oil palm seedlings and reduces 30% of inorganic fertilizers application.